mRNA lipid nanoparticle-mediated pyroptosis sensitizes immunologically cold tumors to checkpoint immunotherapy - Fengqiao Li; Xue-Qing Zhang; William Ho; Maoping Tang; Zhongyu Li; Lei Bu; Xiaoyang Xu (Nature Communications, 2023)
Abstract Synergistically improving T-cell responsiveness is promising for favorable therapeutic outcomes in immunologically cold tumors, yet current treatments often fail to induce a cascade of cancer-immunity cycle for effective antitumor immunity. Gasdermin-mediated pyroptosis is a newly discovered mechanism in cancer immunotherapy; however, cleavage in the N terminus is required to activate pyroptosis. Here, we report a single-agent mRNA nanomedicine-based strategy that utilizes mRNA lipid nanoparticles (LNPs) encoding only the N-terminus of gasdermin to trigger pyroptosis, eliciting robust antitumor immunity. In multiple female mouse models, we show that pyroptosis-triggering mRNA/LNPs turn cold tumors into hot ones and create a positive feedback loop to promote antitumor immunity. Additionally, mRNA/LNP-induced pyroptosis sensitizes tumors to anti-PD-1 immunotherapy, facilitating tumor growth inhibition. Antitumor activity extends beyond the treated lesions and suppresses the growth of distant tumors. We implement a strategy for inducing potent antitumor immunity, enhancing immunotherapy responses in immunologically cold tumors.